The Anti-Myogenic Role of Tetranectin and Its Inhibition by Epigallocatechin-3-Gallate Enhances Myogenesis - Amar Akash; Jihoe Kim (Cells)
Tetranectin (TN) is a plasminogen-binding protein found in human serum. Although it has been suggested to be closely related to various stem cell differentiation, including myogenesis, the role of TN in muscle development remains unclear. In this study, we identified TN as an anti-myogenic factor during the differentiation of C2C12 satellite cells. The exogenous supplementation of TN inhibited myogenic differentiation, whereas differentiation was significantly enhanced in the TN-depleted medium. Epigallocatechin-3-gallate (EGCG), a catechin abundant in green tea, significantly enhanced myogenic differentiation by reducing TN levels in the medium and downregulating TN gene expression during the differentiation process. These results demonstrate that EGCG promotes myogenesis by inhibiting TN at both the transcriptional and functional levels, highlighting TN as a promising therapeutic target for muscle regeneration disorders.